2022
DOI: 10.3390/jcm11051309
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes of Long COVID Symptoms and Clinical Utility of Serum Antibody Titers for Evaluation of Long COVID

Abstract: Background: Various symptoms persist even after the acute symptoms in about one third of patients with COVID-19. In February 2021, we established an outpatient clinic in a university hospital for patients with long COVID and started medical treatment for sequelae that persisted one month or more after infection. Methods: To determine the key factors that affect the onset and clinical course of sequelae, a retrospective analysis was performed at Okayama University Hospital (Japan) between February and July 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…To provide comprehensive treatment and care for these patients, we established a COVID-19 aftercare clinic (CAC) at Okayama University Hospital in February 2021, and we analyzed the characteristics of patients and their clinical courses. Our previous study revealed that general fatigue recollecting myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) was a major complaint in more than half of the patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To provide comprehensive treatment and care for these patients, we established a COVID-19 aftercare clinic (CAC) at Okayama University Hospital in February 2021, and we analyzed the characteristics of patients and their clinical courses. Our previous study revealed that general fatigue recollecting myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) was a major complaint in more than half of the patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that patients in the ME/CFS group had a longer time between the onset of COVID-19 and the first visit (4.2 months in the ME/CFS group vs. 2.5 months in the non-ME/CFS group as shown in Table 1 ) and had higher FAS (38 vs. 28, p < 0.0001), lower quality of life scores (0.6556 vs. 0.7840, p = 0.0001) and higher SDS (50 vs. 46, p = 0.0011) at the time of the first visit as shown in Table 2 . Our earlier studies for patients visiting our CAC [ 6 , 25 ] and a study conducted at another institution [ 5 ] also showed that the most frequent complaint in patients immediately after the onset of COVID-19 was fatigue and that the percentage of patients complaining of fatigue decreased over time, suggesting that patients transitioning from long COVID to ME/CFS may have long-lasting symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…We have recently reported clinical characteristics of PCC patients who visited our COVID-19 aftercare outpatient clinic (CAC). We found that the major sequelae were fatigue and anxiety [ 5 , 10 ] in the early period of the COVID-19 pandemic, that the severity of the acute infection greatly affects the persistent symptoms of PCC [ 11 ], and that some endocrine dysfunction may be involved in the fatigue symptoms of PCC [ 12 , 13 ]. However, the characteristics of PCC patients who were infected with the Omicron variants and the transitional changes in the variant-related symptoms have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%